Key traits for ruminant livestock across diverse production systems in the context of climate change: Perspectives from a global platform of research farms - Rivero, M.J.; López Villalobos, N.; Evans, A.; Berndt, Alexandre; Cartmill, A.; Neal, A.L.; McLaren, A.; Farruggia, A.; Mignolet, C.; Chadwick, David R.; Styles, David; McCracken, D.; et al. (Commonwealth Scientific and Industrial Research Organisation, 2021)
Ruminant livestock are raised under diverse cultural and environmental production systems around the globe. Ruminant livestock can play a critical role in food security by supplying high-quality, nutrient-dense food with little or no competition for arable land while simultaneously improving soil health through vital returns of organic matter. However, in the context of climate change and limited land resources, the role of ruminant-based systems is uncertain because of their reputed low efficiency of feed conversion (kilogram of feed required per kilogram of product) and the production of methane as a by-product of enteric fermentation. A growing human population will demand more animal protein, which will put greater pressure on the Earth’s planetary boundaries and contribute further to climate change. Therefore, livestock production globally faces the dual challenges of mitigating emissions and adapting to a changing climate. This requires research-led animal and plant breeding and feeding strategies to optimise ruminant systems. This study collated information from a global network of research farms reflecting a variety of ruminant production systems in diverse regions of the globe. Using this information, key changes in the genetic and nutritional approaches relevant to each system were drawn that, if implemented, would help shape more sustainable future ruminant livestock systems.